2018
DOI: 10.1016/j.neubiorev.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and circadian disruption and incident breast cancer risk: An evidence-based and theoretical review

Abstract: Opportunities for restorative sleep and optimal sleep-wake schedules are becoming luxuries in industrialized cultures, yet accumulating research has revealed multiple adverse health effects of disruptions in sleep and circadian rhythms, including increased risk of breast cancer. The literature on breast cancer risk has focused largely on adverse effects of night shift work and exposure to light at night (LAN), without considering potential effects of associated sleep disruptions. As it stands, studies on breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 185 publications
(211 reference statements)
0
68
0
3
Order By: Relevance
“…Mots-clés: Sommeil, Heure du Coucher, Durée du Sommeil, Qualité du Sommeil, Qualité du Sperme, Fertilité masculine Background A growing number of studies indicate an association between poor sleep and negative health outcomes. These include increased risk of cardio-metabolic complications, hypertension, obesity, type 2-diabetes, cardiovascular disease, urologic complications, cancer, and depression [1][2][3][4][5][6]. Results from a limited number of recent studies suggest that inadequate bedtimes, short sleep duration, and poor sleep, assessed as poor self-reported sleep quality, may impact semen quality [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Mots-clés: Sommeil, Heure du Coucher, Durée du Sommeil, Qualité du Sommeil, Qualité du Sperme, Fertilité masculine Background A growing number of studies indicate an association between poor sleep and negative health outcomes. These include increased risk of cardio-metabolic complications, hypertension, obesity, type 2-diabetes, cardiovascular disease, urologic complications, cancer, and depression [1][2][3][4][5][6]. Results from a limited number of recent studies suggest that inadequate bedtimes, short sleep duration, and poor sleep, assessed as poor self-reported sleep quality, may impact semen quality [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the biological role of many of the genetic variants used to instrument these traits in Mendelian randomization and mechanistic pathways underlying the observed effects are not well understood. Previously reported pathways between sleep disruption and mammary oncogenesis include immunological, molecular, cellular, neuroendocrine and metabolic processes (5). Further work to uncover these possible mediating processes is required.…”
Section: Discussionmentioning
confidence: 99%
“…However, much of the evidence for the carcinogenic effect of shift work comes from animal models rather than epidemiological or experimental studies in humans (1, 4). Furthermore, while the literature on breast cancer risk has focused on the potentially adverse effects of night shift work and exposure to light-at-night, there has been much less investigation into the potential adverse effects of sleep disruption and traits such as chronotype (morning/evening preference), sleep duration and insomnia (5).…”
Section: Introductionmentioning
confidence: 99%
“…4 Since then, additional and better-documented epidemiologic studies, genome-wide association studies (GWAS) and cellular and animal studies confirmed the link between BCs development and circadian disruption. 5 A recent population-based case-control study confirms that factors including night work duration, length of shifts and time since last night shift affect the odd ratios for BC mostly in premenopausal women. 6 The hormonal receptor status is also important and BC risk associated with night work is only higher for ER+ HER2+ cancer.…”
Section: Introductionmentioning
confidence: 89%